Sowing Qualities of Seeds from Selected Robinia pseudoacacia L. Clones - Proletka Dimitrova; Nikolay Stoyanov (Bulgarian Journal of Soil Science, 2022)
Aim of this study is to analyse the sowing qualities from six selected Robinia pseudoacacia L. clones from the seed orchard on the territory of State Forest Enterprise Parvomay (Plovdiv district). Laboratory and soil germination, energy of germination and sowing norms were investigated. Results show difference in the investigated indices between the separate clones, which probably are genetically determined. Soil germination is with about 18% lower than the laboratory one. Clones suitable for production of black locust seedlings are Jaszkiseri, Appalachiа and Pordim-4, whose genetic settings provide higher germination qualities of seeds compared to the rest of the clones.